30 : 2: A Game Designed to Promote the Cardiopulmonary Resuscitation Protocol - Imma Boada; Antonio Rodriguez-Benitez; Juan Manuel Garcia-Gonzalez; Santiago Thió-Henestrosa; Mateu Sbert (International Journal of Computer Games Technology)
Cardiopulmonary resuscitation (CPR) is a first-aid key survival technique used to stimulate breathing and keep blood flowing to the heart. Its effective administration can significantly increase the survival chances of cardiac arrest victims. We propose 30 : 2, a videogame designed to introduce the main steps of the CPR protocol. It is not intended for certification and training purpose. Driven by the 2010 European Resuscitation Council guidelines we have designed a game composed of eight mini games corresponding to the main steps of the protocol. The player acts as a helper and has to solve a different challenge. We present a detailed description of the game creation process presenting the requirements, the design decisions, and the implementation details. In addition, we present some first impressions of our testing users (25 children, five of each age from 8 to 12 years old and 12 males and 13 females). We evaluated clarity of instructions and three settings of the game: the aesthetics of scenarios, the playability, and the enjoyability of each mini game. All games were well punctuated, and there are no significantly differences between their sex. The proposed game can be a suitable tool to disseminate and promote CPR knowledge.